Controlled Attenuation Parameter and Liver Stiffness Measurements for Steatosis Assessment in the Liver Transplant of Brain Dead Donors. Issue 8 (August 2015) - Mancia, Claire; Loustaud-Ratti, Véronique; Carrier, Paul; Naudet, Florian; Bellissant, Eric; Labrousse, François; Pichon, Nicolas
<x xml:space="preserve">Abstract</x> Background One of the main selection criteria of the quality of a liver graft is the degree of steatosis, which will determine the success of the transplantation. The aim of this study was to evaluate the ability of FibroScan and its related methods Controlled Attenuation Parameter and Liver Stiffness to assess objectively steatosis and fibrosis in livers from brain-dead donors to be potentially used for transplantation. Methods Over a period of 10 months, 23 consecutive brain dead donors screened for liver procurement underwent a FibroScan and a liver biopsy. Results The different predictive models of liver retrievability using liver biopsy as the gold standard have led to the following area under receiver operating characteristic curve: 76.6% (95% confidence intervals [95% CIs], 48.2%-100%) when based solely on controlled attenuation parameter, 75.0% (95% CIs, 34.3%-100%) when based solely on liver stiffness, and 96.7% (95% CIs, 88.7%-100%) when based on combined indices. Conclusions Our study suggests that a preoperative selection of brain-dead donors based on a combination of both Controlled Attenuation Parameter and Liver Stiffness obtained with FibroScan could result in a good preoperative prediction of the histological status and degree of steatosis of a potential liver graft.